A Critical Review on New Approaches for Chronic Disease Prevention in Brazil and Canada: From Wholistic Dietary Guidelines to Physical Activity Security - Schwartz, Juliano; Oh, Paul; Perotto, Maira B.; Rhodes, Ryan E.; Firth, Wanda; Bredin, Shannon S. D.; Gaytán-González, Alejandro; Warburton, Darren E. R. (Frontiers in Cardiovascular Medicine, 2021)
In light of new evidence on the prevention of chronic diseases and the elevated rates of overweight and obesity in Brazil and Canada, this critical review aims to interpret and synthesize current aspects regarding dietary and physical activity initiatives in both countries and make future recommendations. The pioneering work presented in the last Brazilian dietary guidelines has been called a model that can be applied globally, given its conceptualization of healthy eating that translates easily to practical guidance. The new Canadian Food Guide has incorporated similar aspects, also putting the country as a leader in dietary guidance. With these new recommendations, citizens in both Brazil and Canada have access to impactful evidence-informed nutritional guidelines. Both documents propose eating patterns that focus not only on health benefits, such as chronic disease prevention, but also incorporate well-being concerning cultural, economic, sociodemographic, biological, and environmental dimensions. A similar approach is required for physical activity to allow individuals to have attainable health and life goals and thereby fully enjoy their lives, regardless of geographical location, health status, and socioeconomic condition, a concept recently described as physical activity security. The holistic dietary guidelines from both countries represent a change in paradigm in public health. Likewise, national evidence-based policies are warranted to reduce disparities in physical activity, allowing healthier and more active lifestyles for everyone.